LEARING CULTURE THROUGH LITERARY - Sherimbetova Mohichehra; Azzamova Nigora (TADQIQOTLAR.UZ, 2024)
Annotation: This article is devoted for significant role of literary texts in facilitating cultural understanding. It emphasizes the manifold benefits of engaging with literary works as a means to deepen cultural competence.